The Lamellar Cells of Vertebrate Meissner and Pacinian Corpuscles: Development, Characterization, and Functions - Suazo, Iván; Vega, José A.; García-Mesa, Yolanda; García-Piqueras, Jorge; García-Suárez, Olivia; Cobo, Teresa (Frontiers in Neuroscience, 2022)
Sensory corpuscles, or cutaneous end organ complexes, are complex structures localized at the periphery of Aβ-axon terminals from primary sensory neurons that primarily work as low-threshold mechanoreceptors. Structurally, they consist, in addition to the axons, of non-myelinating Schwann-like cells (terminal glial cells) and endoneurial- and perineurial-related cells. The terminal glial cells are the so-called lamellar cells in Meissner and Pacinian corpuscles. Lamellar cells are variably arranged in sensory corpuscles as “coin stack” in the Meissner corpuscles or as "onion bulb" in the Pacinian ones. Nevertheless, the origin and protein profile of the lamellar cells in both morphotypes of sensory corpuscles is quite similar although differs in the expression of mechano-gated ion channels as well as in the composition of the extracellular matrix between the cells. The lamellar cells have been regarded as supportive cells playing a passive role in the process of genesis of the action potential, i.e., the mechanotransduction process. However, they express ion channels related to the mechano-electric transduction and show a synapses-like mechanism that suggest neurotransmission at the genesis of the electrical action potential. This review updates the current knowledge about the embryonic origin, development modifications, spatial arrangement, ultrastructural characteristics, and protein profile of the lamellar cells of cutaneous end organ complexes focusing on Meissner and Pacinian morphotypes.